Enterprise architecture (Software architecture hour (O'Reilly (Firm)), 2021)
There’s one activity that will move your architecture modernization needle more than any other: make the right thing to do the easiest thing to do. So how do you actually do it? Should applications only use approved programming languages? Ensure those languages have a paved road from commit to prod. Should applications only use approved frameworks and libraries? Create automated templates for starting new projects with those frameworks and libraries. Should developers only use the latest versions of approved tools, plug-ins, etc.? Make installing those tools easy, make upgrading those tools automatic. Should developers only leverage specific patterns and shared services? Make learning and using these patterns discoverable, easy, and authoritative. These are only a few examples. But once you start thinking this way, the list of high-value improvements you can start tomorrow writes itself. Join us for a special conversation with Neal Ford and longtime enterprise IT veteran Matt Stine to explore the highest-leverage work you can do to improve your enterprise software architecture. This is a chance for you to ask Neal and Matt anything you want about architecture and their own career journeys. They’ll spend a few minutes covering the trends in enterprise software architecture, then tell you what you need to know to stay ahead of the curve.